Accurate Characterization of Microstrip Filter and Hybrid-Ring Coupler via an Improved TLM Method USing Variable and Curved Meshes - Isele, Bertram; Bender, Harald; Weigel, Robert; Hausner, Josef; Russer, Peter (21st European Microwave Conference, 1991, 1991)
A microstrip circuit design tool based on the two-dimensional transmission-line matrix (2D-TLM) method is described. The TLM algorithm described in this paper incorporates variable and curved discretization meshes and fast Fourier transform (FFT) with zero-padding. Numerical results have been computed for two planar configurations, an 11th order low-pass filter with a design cut-off frequency of 6.6 GHz, and a four-port 3 dB hybrid-ring coupler with a design center frequency of 12 GHz. These circuits were fabricated in hardboard thin-film technology (Â¿ = 9.9), and measurements made with an HP8510 network analyzer were compared with our TLM results, other theoretical analysis, and commercial software data. We found that the 2D-TLM results are in close agreement with generalized scattering matrix analysis and with experimental results.
elib2cris::1512001600,isele1991
Keywords: Circuit synthesis; Coupling circuits; Cutoff frequency; Fast Fourier transforms; Low pass filters; Microstrip filters; Software measurement; Thin film circuits; Transmission line matrix methods; Transmission lines